MANAJEMEN PERSEDIAAN BAHAN BAKU KACANG HIJAU KUE PIA PADA INDUSTRI âANIRAHâ KELURAHAN LASOANI KECAMATAN PALU TIMUR KOTA PALU - Mustari, Mustari; Kalaba, Yulianti (AGROTEKBIS, 2018)
This research aimed to determine the economic order quantity of raw material inventory, the amount of safety stock and the length of time for Re Order Points (ROP)at the Anirahindustry in Lasoani Village, East Palu Subdistrict, Palu City. The analytical tool used were EOQ (Economic Order Quantity), SS (Safety Stock), and ROP (Re Order Point). The results of Â the research indicate that the economical amount of purchasing of the green bean raw materials were 86.06 kg, 66.03 kg and 56.56 kg, respectively, during February to March 2017.The safety stock to be maintained in warehouse at the Anirah industry was 5 kg. The point of return orders must be satisfied were 17 kg, 11,00 kg,and 9,71 kg, respectively, in the months of January, February, and March.Â Keywords: Industry, Palu, Supply Management.